Open Access and its impact on the Knowledge Society: Latin American Case Studies Insights - María Soledad RAMÍREZ MONTOYA (Ediciones Universidad de Salamanca, 2015)
In a changing society, open access may represent an alternative growth and resources to the educational community, from the opportunities given to students, to teachers, researchers and administrators of educational institutions. The aim of this paper is to analyze the opportunities and challenges that gives open access to the educational community, through the presentation of a conceptual vision and practical cases in Latin America, on the issue of open educational resources, repositories, journals and open access policies -from universities and government agencies or financing- and its link to a knowledge society. The findings are presented on three key elements: opportunities, challenges and opportunities open to access the knowledge society.